Analisis Kinerja Lembaga Amil Zakat Infak Sedekah (Lazis) Muhammadiyah Pusat Dengan Pendekatan Balanced Scorecard - Wildan Afifah Haki; Iwan Setiadi; Amrizal Amrizal; Saiful Anwar; Amie Amelia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Zakat is an obligation in Islam that plays a crucial role in the economy and social justice. Through professional management by institutions like Lazis Muhammadiyah, zakat can reduce poverty and enhance community welfare. This study aims to evaluate zakat management performance using the Balanced Scorecard (BSC) approach to ensure efficiency and effectiveness in achieving social goals. The BSC method is used to plan, control, and evaluate organizations from four perspectives: financial, customer, internal processes, and learning. A qualitative descriptive analytical approach is applied to describe the condition of Lazis Muhammadiyah Pusat, collecting primary and secondary data through questionnaires and interviews involving the Executive Director, Muzakki, and staff of Lazis Muhammadiyah Pusat. The research findings indicate that the performance of Lazis Muhammadiyah Pusat, based on the BSC, is very good. Financial receipts reached 74%, customer satisfaction index stands at 90%, and internal innovation level achieved 100%. This reflects the institution's commitment to developing services that are responsive to technological advancements and community needs. Additionally, employee satisfaction reached 83%, reflecting comfort and good relationships among them, which positively impacts work productivity. These findings underscore the importance of professional zakat management in enhancing welfare and social justice